Kajian Hermeneutis Ungkapan â€œSungguh Amat Baikâ€ dalam Kejadian 1:31 Ditinjau dari Perspektif Redemptive-Historical Approach - Jhon Leonardo Presley Purba; Hizkia Febrian Prastowo; Robinson Rimun (Sekolah Tinggi Teologi Anugrah Indonesia, 2022)
AbstractThe phrase â€œit was very goodâ€ in Genesis 1:31 is a phrase that has important theological and historical significance in the redemptive historical of Christ. The history of redemption itself, as a hermeneutical approach, cannot be separated from the events of creation. Presented in a qualitative descriptive form with the method of literature study and grammatical textual analysis, this article is intended to do a hermeneutical study of the expression â€œit was very goodâ€ in Genesis 1:31, which is carried out from the perspective of the redemptive historical approach, to then find its theological and historical meaning. The results of this study conclude that based on a hermeneutical study from the perspective of the redemptive historical approach, the expression â€œit was very goodâ€ in Genesis 1:31 has two important meanings, first, the theological meaning in terms of genealogy/origins of creation where this expression is God's qualitative assessment of the quality of all creation that is perfect, complete and harmonious, which reflects the quality of God as the Creator. Second, the historical meaning which is viewed from the eschatology of Christ's redemption where this expression is the beginning of history which progressively, after the fall of man into sin, also acts as the beginning and end of the history of redemption. The phrase â€œit was very goodâ€ is the ultimate goal/ultimate quality of all creation that Christ has redeemed. Christ's redemptive work restores the quality of the value of creation to its original state, as God intended from the beginning.AbstrakUngkapan â€œsungguh amat baikâ€ dalam Kejadian 1:31 merupakan frasa yang memiliki makna teologis dan historis yang penting dalam sejarah penebusan Kristus. Sejarah penebusan sendiri sebagai suatu pendekatan hermeneutis, tidak dapat dipisahkan dari peristiwa penciptaan. Disajikan dalam bentuk kualitatif deskriptif dengan metode studi literature dan analisis tekstual grammatical, tulisan dimaksudkan untuk melakukan kajian hermeneutis terhadap ungkapan â€œsungguh amat baikâ€ dalam Kejadian 1:31, yang dilakukan dari perspektif redemptive historical approach, untuk kemudian menemukan makna teologis dan historisnya. Hasil penelitian ini menyimpulkan bahwa berdasarkan kajian hermeneutis dari perspektif redemptive historical approach, ungkapan â€œsungguh amat baikâ€ dalam Kejadian 1:31 memiliki dua makna penting yaitu pertama, makna teologis ditinjau dari silsilah/asal-usul penciptaan dimana ungkapan ini merupakan penilaian kualitatif Allah atas kualitas segala ciptaan yang sempurna, utuh dan harmonis, yang mencerminkan kualitas Allah sebagai Pencipta. Kedua, makna historis yang ditinjau dari eskatologis penebusan Kristus dimana ungkapan ini merupakan awal dari sejarah yang secara progressive, setelah kejatuhan manusia dalam dosa, juga berperan sebagai awal dan tujuan akhir sejarah penebusan. Ungkapan â€œsungguh amat baikâ€ merupakan tujuan akhir/kualitas akhir segala ciptaan yang telah ditebus Kristus. Karya penebusan Kristus mengembalikan kualitas nilai ciptaan kepada keadaanya yang semula, sebagaimana Allah maksudkan sejak awal.